Issues of Improving the Organizational and Economic Mechanism at Building Materials Industry Enterprises - Isayev Jakhongir Muzaffarovich (Researchparks Publishing, 2022)
This article analyzes the possibilities and prospects for improving the organizational and economic mechanism at the enterprises of the building materials industry in modern economic conditions. Proposals are made regarding the activities to be carried out under the mechanism.